Curriculum analysis process: Analysing fourteen industrial engineering programs - Lima, Rui M. (2019)
The fourth industrial revolution is demanding for new competences, thus requiring curricula redesign. A comprehensive analysis of current curricula contributes for the design of the new foreseen curricula. According to Hoffman (1999, p. 283): “the design of learning programs may be based on the inputs needed or the outputs demanded”. Thus, curriculum analysis is helpful to identify aspects that are working and those that need a change (Wolf, Hill, & Evers, 2006). This purpose is crucial in the context of Industry 4.0, in order to prepare future engineers to face the challenges of their practice. Considering that in Europe, in general, formal curriculum level presents the structural aspects (e.g. hours and number of courses) and the learning outcomes of each course, it is possible to identify the areas of knowledge and the competences students are expected to develop. This paper aims to make a curriculum analysis, based on areas of knowledge and learning outcomes. This was based on a process exploring information from the formal level of curriculum that can be replicated in other contexts. Additionally, the process was applied to fourteen European Industrial Engineering master programs. The results show that there is a high level of diversity regarding main areas of knowledge and technical competences of each program. Moreover, it showed an enormous lack of attention in terms of transversal competences in all programs.